The Gustavus Gene Can Regulate the Fecundity of the Green Peach Aphid, Myzus persicae (Sulzer) - Gao, Yang; Ren, Ruifan; Peng, Jing; Wang, Dongwei; Shi, Xiaobin; Zheng, Limin; Zhang, Zhuo; Zhu, Chunhui; Liu, Yong; Dai, Liangying; Zhang, Deyong (Frontiers in Physiology, 2021)
Myzus persicae (Sulzer), commonly known as the green peach aphid, is a notorious pest that causes substantial losses to a range of crops and can transmit several plant viruses, including potato virus Y (PVY). Chemical insecticides provide only partial control of this pest and their use is not environmentally sustainable. In recent years, many genes related to growth, development, and reproduction have been used as targets for pest control. These include Gustavus (Gus), a highly conserved gene that has been reported to play an essential part in the genesis of germline cells and, hence, in fecundity in the model insect Drosophila melanogaster. We hypothesized that the Gustavus (Gus) gene was a potential target that could be used to regulate the M. persicae population. In this study, we report the first investigation of an ortholog of Gus in M. persicae, designated MpGus, and describe its role in the fecundity of this insect. First, we identified the MpGus mRNA sequence in the M. persicae transcriptome database, verified its identity with reverse transcription-polymerase chain reaction (RT-PCR), and then evaluated the transcription levels of MpGus in M. persicae nymphs of different instars and tissues with real-time quantitative PCR (RT-qPCR). To investigate its role in regulating the fecundity of M. persicae, we used RNA interference (RNAi) to silence the expression of MpGus in adult insects; this resulted in a significant reduction in the number of embryos (50.6%, P<0.01) and newborn nymphs (55.7%, P<0.01) in the treated aphids compared with controls. Interestingly, MpGus was also significantly downregulated in aphids fed on tobacco plants that had been pre-infected with PVYN, concomitant with a significant reduction (34.1%, P<0.01) in M. persicae fecundity. Collectively, these data highlight the important role of MpGus in regulating fecundity in M. persicae and indicate that MpGus is a promising RNAi target gene for control of this pest species.